Renal diseases in children at the university of Gondar hospital, Ethiopia: pattern and outcome - Alemu, Mehretie K.; Dubie, Addisu G. (International Journal of Contemporary Pediatrics, 2024)
Background: In developing countries, renal diseases in children are becoming common causes of morbidity and mortality. In Ethiopia, there are no adequate data about patterns and outcome of these disorders. We conducted this study to provide evidences on patterns and outcome of renal diseases in children admitted to a tertiary hospital in Gondar, Ethiopia. Methods: A retrospective record review of all pediatric patients admitted with renal diseases over a period of two-years (January 2022-December 2023) to the university of Gondar hospital (UoGH), was conducted. Results: A total of 456, comprising 231 (50.7%) females and 225 (49.3%) males, patients were studied. Majority (37.7%) of patients were below 5 years of age. Renal diseases accounted for 3.6% of all admissions during the 2-years period. Common renal problems were urinary tract infection (UTI) (29%), acute glomerulonephritis (AGN) (24.1%), nephrotic syndrome (18.6%), acute kidney injury (AKI) (14.3%), nephroblastoma (9%) and chronic kidney diseases (CKD) (2.4%). Finally; 71.9% were discharged improved and 10.5% died. The highest case fatality rates were in patients with rapidly progressive glomerulonephritis (36.7%) followed by CKD (36.4%), and AKI (21.5%). Conclusions: This study revealed high prevalence and mortality rate of renal diseases in children. The major causes of death were AGN/RPGN, CKD and AKI. All the above evidences clearly disclosed that establishment of a pediatric nephrology unit and get a trained pediatric nephrologist in our university hospital is critical.